PEMBERIAN AMELIORAN PADA BIBIT KELAPA SAWIT (ELAEIS GUIENEENSIS JACQ.) DI PEMBIBITAN AWAL - Marlia ' Kholifah; Sampoerno ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to determine the best ameliorant influence on the growth of oil palm seedlings in the pre nursery. This research was conducted at the Agriculture Experiment Station of Agriculture Faculty University of Riau, from February to May 2015. The treatment were consisted of 4 ameliorants, ie: A0 : without giving ameliorant , A1 : Ameliorant ash janjangan palm oil 10 g / polybag , A2 : Ameliorant compost tangkos 10 g / polybag , A3 : Ameliorant sludge palm oil mill 10 g / polybag , A4 : Ameliorant ash boiler 10 g / polybag. Parameters measured were seedling height , number of leaves , leaf length and hump diameter. The result of the research showed that the provision of some kind of material ameliorant significant effect on seedling height , number of leaves , leaf length and hump diameter.  Giving sludge palm oil 10g / polybag is the best treatment effect on seedling height (24 cm) , the number of leaves (4.62 leaves), leaf length (19.97 cm) and hump diameter (1,5 cm).   Key word : oil palm, ameliorant, pre-nursery.